Feasibility Study on the Development of Cabangbungin Regional General Hospital, Bekasi Regency, from Class D to Class C - Herdiani, Erni; Aziz, Abdul; Supardjo, Supardjo (IJBLE Scientific Publications Community Inc., 2025)
This study analyzes the feasibility of establishing RSUD Cabangbungin in Bekasi Regency, focusing on investment requirements, funding sources, financial projections, and cash flow analysis. The total investment needed amounts to IDR 108.78 billion, sourced from BLUD for the addition of 12 hospital beds and APBD for the construction of 38 hospital beds. The financial analysis indicates that RSUD Cabangbungin will initially operate at a deficit, with projected losses in the first three years. However, profitability is expected to begin in the fourth year, with a net profit of IDR 1.44 billion, increasing to IDR 4.03 billion by the fifth year. The cash flow analysis demonstrates a positive trend, with cumulative net cash increasing each year, reaching the break-even point within five years. These findings suggest that the RSUD Cabangbungin project is financially feasible and sustainable in the long run. Effective management strategies, pricing adjustments, and operational efficiency are essential to maximizing profitability and ensuring the hospital's role in providing quality healthcare services to the community.